Integrasi Aliran Teori Belajar Utama dalam Pendidikan Islam: Telaah Aliran Proses Informasi, Behaviorisme, Kognitivisme, Konstruktivisme, dan Humanisme - Ibrahim Ibrahim; Tajuddin Hamzah; Kasinyo Harto; Mardiah Astuti (Universitas Islam Negeri Sumatera Utara Medan, 2026)
Islamic education in the contemporary and digital era faces complex challenges that require adaptive, holistic, and value-oriented pedagogical approaches. Relying on a single learning theory is no longer sufficient to develop learners’ intellectual, moral, spiritual, and social dimensions simultaneously. This study aims to examine the integration of major learning theories—behaviorism, information processing theory, cognitivism, constructivism, and humanism—within the framework of Islamic education. Using a qualitative descriptive approach through library research, this study analyzes and synthesizes relevant theoretical literature on learning theories and Islamic educational principles. The findings indicate that each learning theory contributes distinct strengths: behaviorism supports the formation of disciplined and habitual religious behavior; information processing theory and cognitivism enhance cognitive development and meaningful understanding; constructivism promotes contextual and experiential learning; while humanism emphasizes personal growth, empathy, and spiritual awareness. When integrated under the foundational value of tauhid, these theories form a comprehensive and balanced learning framework. This integrative model enables Islamic education to respond effectively to modern challenges without losing its core identity, aiming to produce learners who are intellectually competent, morally grounded, emotionally mature, and spiritually aware.